Parents’ satisfaction and the quality of dental care provided by dental students at International Islamic University Malaysia - Yeon, Asilah Anis; Kamaruddin, Athirah; Harun, Nor Asilah; Kusumawardani, Anisa (S Bland, 2019)
Little is known about the relation between patients’ satisfaction and quality of care they received, therefore the aim of this study was to assess the relation between parents’ satisfaction and quality of dental care provided by dental students at IIUM Polyclinic during clinical session. A self-administered questionnaire were distributed to parents who attended their children. The students’ performances were assessed by a lecturer. 42 questionnaires and assessment forms were analysed. Generally, parents are satisfied with the dental care regardless of the quality therefore parents’ satisfaction could not be the tool to assess the quality of care provided by the operators.